A BEHAVIORAL APPROACH TO BILATERAL COOPERATION ON CRIMINAL LAWS: A CASE STUDY ON INDONESIA’S EXTRADITION AND MUTUAL LEGAL ASSISTANCE TREATIES - Citrawan, Harison; Fedian, Muhammad (UI Scholars Hub, 2020)
The effectiveness of bilateral agreements in the context of criminal law enforcement remains highly contested. In the Indonesian context, such bilateral cooperation classifies two modalities of indirect law enforcement systems, namely, extradition and mutual legal assistance (MLA) in criminal matters. This article attempts to explain these modalities through a behavioral and rational approach by taking Indonesia’s MLA treaty with Switzerland and its extradition treaty with the Russian Federation as a case study. From this approach, we argue that the state’s decision to cooperate implies the adoption of control and consensus models. However, these two models were induced by political preferences rather than the sole reliance on the maxim aut dedere aut judicare in criminal laws. At the domestic level, the attitudes of penal entrepreneurship and institutional arrangement showcase the multifaceted state’s rationality in deciding a treaty design in criminal law cooperation.